Evaluasi penatausahaan barang milik daerah berdasarkan Permendagri Nomor 47 Tahun 2021 pada Sekretariat Dewan Perwakian Rakyat Daerah Kota Manado - Lucas, Kanaya Zefanya Laeticia Rachel; Afandi, Dhullo; Kapojos, Peter M. (Yayasan Widyantara Nawasena Raharja, 2025)
Minister of Home Affairs Regulation Number 47 of 2021 is the standard basis for recording the Procedures for Implementing Bookkeeping, Inventory and Reporting of Regional Property. Minister of Home Affairs Regulation Number 47 of 2021 improves previous regulations by examining implementation and developments in the field. This ensures the successful implementation of the transition works, resolving regional property problems and achieving better administration than before.This research aims to evaluate the suitability of the administration of regional property at the Manado City Regional People's Representative Council Secretariat with the Home Affairs Government Number 47 of 2021.The research uses the descriptive analysis method to discuss the problems. The results show that the inventory procedure in the process of data collection, recording and reporting of inventory results as a whole has carried out the process in accordance with Minister of Home Affairs Regulation Number 47 of 2021. The inventory process at the Manado City Regional People's Representative Council Secretariat is hindered by the use of the SIMDA regional property application, which has not yet been implemented. This hinders the input of regional property data, as outlined in Minister of Home Affairs Regulation Number 47 of 2021.